2015
DOI: 10.1007/s00404-015-3768-0
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant management of pregnant women with mechanical heart valve replacement during perioperative period

Abstract: The use of vitamin K1 preoperatively might result in warfarin resistance and discontinuation of warfarin therapy before selective CS might be more appropriate than application of vitamin K1. The "bridging" anticoagulation treatment which combines oral warfarin and subcutaneous LMWH might be more effective and safer than single oral warfarin therapy for patients with mechanical heart valve replacement during postoperative period, no matter selective or emergency CS. The safety of low-dose oral warfarin therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 16 publications
(16 reference statements)
0
20
0
Order By: Relevance
“…After duplicate removal, 247 studies were identified through database search and screened by title and abstract. A total of 37 studies were finally included 1 2 3 5 8 10 12 13 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ( Table 1 ). In 22 of the included studies, data were retrospectively collected, 6 10 12 13 17 18 19 20 21 23 24 25 26 28 32 36 37 38 40 41 42 43 44 whereas 15 studies collected data prospectively.…”
Section: Resultsmentioning
confidence: 99%
“…After duplicate removal, 247 studies were identified through database search and screened by title and abstract. A total of 37 studies were finally included 1 2 3 5 8 10 12 13 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ( Table 1 ). In 22 of the included studies, data were retrospectively collected, 6 10 12 13 17 18 19 20 21 23 24 25 26 28 32 36 37 38 40 41 42 43 44 whereas 15 studies collected data prospectively.…”
Section: Resultsmentioning
confidence: 99%
“…The overall incidence of prosthetic valve thrombosis in mitral or aortic position at any time is 0.5-6% in developing countries, being the highest in mitral position, while in developed countries the prevalence is 0.3-1.3% [1][2][3][4]. Patient-related risk factors for prosthetic valve thrombosis are: inadequate anticoagulation, left ventricular dysfunction, atrial fibrillation, pregnancy (hypercoagulability status), infection, early postoperative period, among others [1][2][3][5][6][7][8], many of which were observed in our case clearly because the patient had inadequate anticoagulation levels over the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery has high-risk factors because it is a reintervention, most often performed under emergency conditions. On the other hand, fibrinolysis carries important risks of bleeding, systemic embolism, and recurrent thrombosis that are higher than after surgery [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an NMA can estimate the rank of these treatments 23 2425 and nine observational studies)26–34 in recent years were not included in these studies, which reduced trustworthiness and statistical power of these studies. Finally, some subgroups of anticoagulation treatments (eg, different VKAs and heparin doses, different combinations of sequential treatments, and type, location and number of MHVs, etc) were not considered in these studies, which led to the lack of results of effectiveness and safety by comparing these subgroups.…”
Section: Introductionmentioning
confidence: 99%